PENGUATAN FUNGSI PEMBENTUKAN PERATURAN DAERAH DI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN KUANTAN SINGINGI - Poni Apri Dila; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Strengthening the function of forming Regional Regulations in the Regional People'sRepresentative Council of Kuantan Singingi Regency in the formation of which there is still alack of Regional Regulations produced by the Regional People's Representative Council in the2014-2019 period. Therefore, it is necessary to study first, the minimum number of RegionalRegulations made, Strengthening the function of forming Regional Regulations in the RegionalPeople's Representative Council of Kuantan Singingi Regency. Second, ideally the role of theRegional People's Representative Council in forming Regional Regulations in KuantanSingingi Regency.This research is classified as sociological juridical research. With the research location atthe Kuantan Singingi Regency Regional People's Representative Council.From the research results, it was concluded that, firstly, the lack of Regional Regulationsproduced by the Regional People's Representative Council was caused by an inadequatebudget, weak function and understanding of the Regional People's Representative Council, thestrong interests of Political Parties and several Regional Regulations that were cancelled.strengthening the function of forming DPRD Regional Regulations, namely allocating thebudget properly, increasing the capacity of the Regional People's Representative Council,increasing coordination between the executive and legislative parties, and strengthening theRegional Regulation Formation Agency. Second, the ideal role of the DPRD in formingRegional Regulations in Kuantan Singingi Regency is to understand the substance of its maintasks and functions, understand and play an active role in the stages of forming RegionalRegulations, and comply with the DPRD's Rules of Procedure.Keywords: Strengthening - Formation of Regional Regulations - Regional People'sRepresentative Council